Toxicity of banana suckers by promisory herbicides for the control of Dieffenbachia oerstedii. - Brenes-Prendas, Steven; Agüero-Alvarado, Renán (Agronomía Mesoamericana, 2012)
Toxicity of banana suckers by promisory herbicides for the control of Dieffenbachia oerstedii. Potential toxicity on banana sword suckers of next treatments was evaluatedbetween August and December of 2006: T1) absolute check, T2) Carfentrazone + surfactant; T3) Glyphosate +surfactant; T4) Glyphosate + carfentrazone + surfactant;T5) Glyphosate + ammonium sulphate + surfactatant; T6) metsulfuron metyl + carfentrazone + surfactant. A complete randomized design was used, with 20 replications for each treatment, for a total of 120 bananas suckers. The treatment with Metsulfuron methyl + carfentrazone + surfactantaffected growth of some suckers and caused death of a few of them. Glyphosate + carfentrazone + surfactant did not differ from the absolute check. The potential of thetreatment with Glyphosate + carfentrazone for Dieffenbachia oerstedii control in commercial fields of banana plantationsis confirmed, because it provides acceptable wweed control and no damage of young banana suckers.